One-stage supraclavicular hybrid procedure for type B aortic dissection involving three rare anatomical anomalies: a case report and literature review. Issue 6 (June 2021) - Chen, Junhang; Dai, Xiangchen; Zhu, Jiechang; Hu, Fanguo; Li, Peng; Luo, Yudong; Fan, Hailun; Feng, Zhou; Zhang, Yiwei
Managing type B aortic dissection (TBAD) involving Kommerell's diverticulum (KD), aberrant right subclavian artery (ARSA), and isolated left vertebral artery (ILVA), is extremely challenging. As treatment, we described a one-stage hybrid technique combined with thoracic endovascular aortic repair (TEVAR) with open surgery through a supraclavicular incision. A 57-year-old man with TBAD and the three anomalies successfully underwent hybrid TEVAR. A side-to-side artificial bypass between the ARSA and the right common carotid artery was established through a right supraclavicular incision before TEVAR. The release of the stent-graft was designed from the distal aortic ostium to the left common carotid artery (LCCA) to cover the ILVA, ARSA, and left subclavian artery (LSA). Then, the ILVA and LSA were transposed to the LCCA through a left supraclavicular incision. Intraoperative angiography confirmed complete false lumen exclusion and KD, with all branches patent and without endoleaks. Computed tomography angiography 7 days and 1 year postoperatively demonstrated well-perfused ARSA, LSA, and ILVA, and a fully expanded stent-graft with no endoleaks, migration, disconnection, or stenosis. TBAD involving KD, ARSA, and ILVA in one case is rare. This is the first report to treat this pathology with a one-stage supraclavicular hybrid procedure.